Evolution of the use of Nanoparticles in Cancer Diagnosis and Treatment (Global Journals of Research in Engineering, 2024)
The use of nanoparticles in the health area is a research topic that has been increasing in recent years from that perspective this work focused on making a characterization of nanoparticles their evolution and interaction with blood aspect addressed through the description of the biomagnetic fluid focusing on characteristics such as viscosity and geometry Also the evolution of the applications or techniques in which nanoparticles have been used is presented focusing the review on cancer treatments for which the four progressive generations of this research field were considered as well as the use of nanoparticles in diagnostic imaging Finally some fields of implementation and study in Colombia were identified The review carried out allows concluding that the evolution of the use of nanoparticles
Keywords: biomagnetic fluid; nanoparticles; magnetic nanoparticles; SPIONs